STANDARDIZATION OF EXTRACT AND CHARACTERIZATION OF EMULGEL FORMULA OF LENGKUAS (Alpinia galanga (L.) Willd) RHIZOME EXTRACT - Widyasari Putranti; Novia Ariani Dewi; Lina Widiyastuti (Sanata Dharma University, 2018)
The lengkuas rhizome has an antifungal activity. The non-specific parameters for extracts of lengkuas rhizome need to be standardized to obtain the extracts with consistent good quality. The lengkuas rhizome extract emulgel topical preparations are easily mixed with active substances that are hydrophobic or hydrophilic. This study aims to obtain a lengkuas rhizome extract emulgel formula that has good quality and good physical properties. Extraction of lengkuas rhizome was obtained using a maceration method with 96% ethanol solvent. The extract is standardized by non-specific parameters. After that, the extract was formulated in the form of emulgel preparation with 10% concentration. The physical properties of emulgel were evaluated. The results of the study showed that the extract yield is of (14.660.056)%; powder drying shrinkage (8.630.134)%; extract water rate (50)%; powder total ash rate (3.240.017)%; and extract (1.300.035)%; acid-insoluble ash rate powder (2.660.10)%; and extract (0.870.031)%; extract type weight 1.01; and the physical properties of emulgel preparations were homogeneous emulgel, semisolid form, light brown color, distinctive smell of lengkuas rhizome extract, stable at 5oC and 25oC for 24 hours; pH 7; spreadability (2.450.03) g.cm.s-1; stickiness (8.800.72) seconds; o/w emulsion type; and viscosity (1.370.22) Pa.s. This study obtained extracts of lengkuas rhizomes that meet the requirements of non-specific parameter standardization in general and the formulation of lengkuas rhizome extract emulgel had good physical properties.